Change in prevalence of gestational diabetes and obstetric complications when applying IADPSG screening criteria in a Belgian French speaking University Hospital. A retrospective cohort study - Elena Costa; Christine Kirckpartick; Colette Gerday; Aricia De Kempeneer; Sara Derisbourg; An Vercoutere; Sophie Haumont; Axelle Pintiaux; Caroline Daelemans (BMC, 2019)
Abstract Background In April 2012 our institution chose to switch from a two- step criteria for Gestational Diabetes Mellitus (GDM) screening, to the International Association of Diabetes in Pregnancy Study Group (IADSPG) criteria. This shift led to an increased prevalence of GDM in our pregnant population. We designed a study in order to estimate the magnitude of the increase in GDM prevalence before and after the switch in screening strategy. As a secondary objective we wanted to evaluate if there was a significant difference between the two periods in the percentage of maternal and neonatal complications such as gestational hypertensive disorders (GHD), primary cesarean section (pCS), preterm birth, large for gestational age (LGA) newborns, macrosomia, shoulder dystocia, 5' Apgar score less than to 7 at birth, neonatal intensive care unit (NICU) transfer and neonatal hypoglycemia. Methods We selected retrospectively 3496 patients who delivered between January 2009 and December 2011 who were screened with the two-step criteria (group A), and compared them to 2555 patients who delivered between January 2013 and December 2014 and who were screened with IADPSG criteria (Group B). We checked patients' electronic files to establish GDM status, baseline characteristics (age, body mass index, nationality, parity) and the presence of maternal and neonatal complications. Results GDM prevalence increased significantly from group A (3.4%; 95%CI 2.8-4.06%) to group B (16.28%; 95%CI 14.8 -17.7%). In group B there were significantly more non-Belgian and primiparous patients. There was no statistically significant difference in maternal and neonatal complications between the two groups, even after adjustment for nationality and parity. There was a non-significant reduction of the proportion of macrosomic and of LGA babies. Conclusions In our population the introduction of IADPSG screening criteria has increased the prevalence of GDM without having a statistically significant impact on pregnancy outcomes.